Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3906/sag-1511-155
|View full text |Cite
|
Sign up to set email alerts
|

An 8-week thoracic spine stabilization exercise program improves postural back pain, spine alignment, postural sway, and core endurance in university students:a randomized controlled study

Abstract: Background/aim: To investigate the effects of an 8-week thoracic stabilization exercise program on back pain, spinal alignment, postural sway, and core endurance in university students.Materials and methods: University students were randomly allocated into exercise (n: 28) and control (n: 25) groups. The exercise program was carried out 3 days a week for 8 weeks. Postural pain, spinal alignment, postural sway, and core endurance were assessed via visual analogue scale, Spinal Mouse, Biodex Balance System, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 59 publications
(96 reference statements)
1
16
0
2
Order By: Relevance
“… 2 In Toprak’s study, 56 university students were randomly allocated to exercise or control groups, and significant differences were observed for postural pain, thoracic and lumbar curvature, and other parameters in the exercise group between baseline and after treatment. 14 Kadono’s study also confirmed that stretching exercise can increase lumbar lordosis angle. 15 Moreover, patients with degenerative disc disease were confirmed to have lower lumbar lordosis and more vertical sacral profiles.…”
Section: Discussionmentioning
confidence: 76%
“… 2 In Toprak’s study, 56 university students were randomly allocated to exercise or control groups, and significant differences were observed for postural pain, thoracic and lumbar curvature, and other parameters in the exercise group between baseline and after treatment. 14 Kadono’s study also confirmed that stretching exercise can increase lumbar lordosis angle. 15 Moreover, patients with degenerative disc disease were confirmed to have lower lumbar lordosis and more vertical sacral profiles.…”
Section: Discussionmentioning
confidence: 76%
“…Exercises can increase the activation of paravertebral muscles, improve the stability and coordination of lumbar spine, improve lumbar lordosis angle and adjust the lumbar alignment and subsequently it can result in the relief of nerve compression, and the symptoms including pain and disability are improved in patients with LSS. 2 , 14 , 15 Compared with exercise therapy, lumbar decompressive laminectomies can relieve pain immediately, but it can’t strengthen the power of muscles and flexibility of joints. In addition, surgical procedures may damage the paravertebral muscles, decrease the muscle power and adversely affect the lumbar alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria are based on similar previous studies. 6,13 This study was conducted at Termal Vocational School, Yalova, Turkey. A total of 125 young adults were examined regarding their eligibility for inclusion in this study.…”
Section: Methodsmentioning
confidence: 99%